A biological additive in granulated mineral compound fertilizer improves productivity of spring wheat and sugar beet - Šlinkšienė, Rasa; Grodickas, Marijus (Frontiers in Sustainable Food Systems, 2025)
The use of biological additives often enhances plant fertilization efficiency and reduces the environmental impact of fertilizers; however, their effectiveness varies depending on the context. It is particularly important that such additives are compatible with mineral fertilizers and remain viable and effective during industrial production. The aim of this study was to develop bulk NPK compound fertilizers supplemented with the biological additive Fosfix, a commercial product from the Lithuanian company Bioenergy LT. This product contains bacteria that help absorb phosphorus from insoluble soil compounds. The study also aimed to evaluate their agronomic effectiveness under field conditions. The fertilizer formulations incorporating the biological additive were developed at Kaunas University of Technology, with the goal of adapting the additive for industrial fertilizer production. Laboratory tests demonstrated that optimal fertilizer characteristics – commercial fraction content of 64–78%, granule strength of 28–41 N per granule, and moisture content of 15–16.5% – were achieved using a raw material mixture containing up to 60% recycled product. These laboratory conditions were successfully applied at pilot scale in industry, and a pilot batch of the developed product was produced in a fertilizer manufacturing company. Agrochemical tests were conducted at the Rumokai Experimental Station, a branch of the Lithuanian Agricultural and Forestry Research Centre. Field tests showed that the biological additive improved the performance of sugar beet (Beta vulgaris L.) variety Severa KWS compared to spring wheat (Triticum aestivum L.) variety Triso: initial germination increased by 6%, root yield by 5.78 t·ha1, and basic sugar yield by 5.16 t·ha−1. In conclusion, the newly developed fertilizer formulations promote plant physiological processes, support the expression of genetic potential, and ensure minimal nutrient loss.